2011
DOI: 10.3892/or.2011.1166
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-associated virus-mediated survivin mutant Thr34Ala cooperates with oxaliplatin to inhibit tumor growth and angiogenesis in colon cancer

Abstract: Abstract. Colon cancer is one of the most common cancers. Survivin is overexpressed in human colon cancer and correlate with chemoresistance, angiogenesis and poor prognosis. Oxaliplatin, a platinum derivative cancer drug, has been used for treating human colorectal cancers. In the present study, we investigated the effect of the adeno-associated virus (AAV)-mediated survivin mutant Thr34Ala [rAAV-Sur-Mut(T34A)] on colon cancer growth. Infection with rAAV-Sur-Mut(T34A) inhibited cell proliferation, induced apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Survivin functions to inhibit cell apoptosis through suppressing the activity of the apoptotic initiator caspase-9, followed by preventing the activation of the apoptotic effector caspase-3 (21). The TmSm proteins could release the activity of caspase-9 and finally achieve the purpose of promoting cell apoptosis (22,23). To gain an understanding of the reason that the anti-cancer capacity of TmSm34/48/84 was weaker than that of TmSm34/84, we used ZDOCK to simulate the docking for three multisite TmSm proteins with caspase-9 (Figure 5).…”
Section: Docking Results For Tmsm Proteins With Caspase-9mentioning
confidence: 99%
“…Survivin functions to inhibit cell apoptosis through suppressing the activity of the apoptotic initiator caspase-9, followed by preventing the activation of the apoptotic effector caspase-3 (21). The TmSm proteins could release the activity of caspase-9 and finally achieve the purpose of promoting cell apoptosis (22,23). To gain an understanding of the reason that the anti-cancer capacity of TmSm34/48/84 was weaker than that of TmSm34/84, we used ZDOCK to simulate the docking for three multisite TmSm proteins with caspase-9 (Figure 5).…”
Section: Docking Results For Tmsm Proteins With Caspase-9mentioning
confidence: 99%
“…Alternatively, intratumor therapeutic delivery inhibited the growth of previously established tumors by 81% and prolonged mean survival of treated mice by 75%. The same group [139] subsequently delivered another dominant-negative survivin mutant capable of inducing apoptosis and reducing tumor growth, T34A, to an HCT-116 human colon cancer mouse model using AAV2 and obtained similar results, with further enhanced therapeutic effects when combining AAV with oxaliplatin (62% of mice showing complete survival). Two other groups [140, 141] also used AAV-mediated delivery of the C84A and T34A survivin mutants, respectively, for in vivo models of gastric cancer and observed reduced tumor growth, increased tumor cell apoptosis, and increased tumor sensitivity to 5-fluoracil.…”
Section: Aav Delivery Of Therapeutic Payloads In Preclinical Models Omentioning
confidence: 92%
“…5-FU treatment has been shown to induce survivin levels; therefore, the authors postulated that overexpression of the dominant-negative survivin with 5-FU treatment resulted in enhanced cytotoxicity [ 76 ]. Furthermore, enhanced tumor cell killing was demonstrated following the rAAV-mediated expression of survivin mutant T34A (rAAV-Sur-Mut(T34A)) and oxaliplatin, used for the treatment of advanced colorectal cancer that is resistant to 5-FU, in colon cancer models in vivo [ 77 ]. Yet another study showed that the combination of 5-FU and rAAV-mediated overexpression of shRNA targeting FHL2 (Four and a half LIM-only protein 2) resulted in increased colon cancer cell death in vivo [ 34 ].…”
Section: Combination Therapy—raav and Chemotherapymentioning
confidence: 99%